Perencanaan Sistem Fire Alarm Semi-Addressable dan Sprinkler pada Bangunan Gedung Fakultas Teknik 3 Universitas Tidar - Vincent Cleo D.A. P,; Bagus Fatkhurrozi,; Sapto Nisworo, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The impact of fire, from property damage to life threats, is devastating. The fire department is generally notified immediately, but delays often occur due to distance. Engineering Faculty Building 3 is not yet equipped with an automatic extinguishing system. An automatic warning and shutdown system is required. Planning completes the FT3 fire protection system, analyzing building characteristics and identifying potential hazards. Analysis according to NFPA standards ensures reliability and safety. The results show FT3 has a Low Fire Hazard Potential, with the danger concentrated in areas of combustible materials that produce little heat, and the fire spreads slowly. System calculation: 67 smoke detectors, 222 sprinklers, water volume 416.35 m3, water tank 500 m3. Pump power includes HHP 35.2 kW, BHP 46.9 kW, P 60 kW, and PpD 27 HP. The budget for developing an automated system at FT3 is around IDR 1,232,640,194.